A 'on-off-on' fluorescent probe for sensitive detection of Fe3+ and ascorbic acid by cross-linking agent protected carbon dots. Issue 1 (2nd January 2022) - Tu, Jianqiu; Yang, Xueying; Liu, Huiping; Chen, Pei; Liu, Kai; Gao, Jie
ABSTRACT: Carbon dots (CDs) have gained great attention as multifunctional materials because of their interesting properties and general applicability. Herein, new CDs were synthesised from a facile hydrothermal treatment of cysteine and ethylene glycol dimethacrylate as both carbon and nitrogen source and cross-linking agent with high quantum yield (47.2%), respectively. The as prepared CDs were used to detect Fe 3+ and ascorbic acid. The fluorescence intensity of CDs was selectivity quenched by Fe 3+ in the range of 0.03–15.0 µM, with a detection limit of 10.2 nM. Meanwhile, ascorbic acid was found to reduce Fe 3+ to Fe 2+, thereby causing restoration of the fluorescence of CDs. The detection limit for ascorbic acid detection was estimated as 54.3 nM over a linear range from 0.1 to 25.0 µM. Furthermore, the designed sensing platform was successfully utilised to the detection of Fe 3+ and ascorbic acid in water and fruits samples.